1974
DOI: 10.1103/physrevlett.33.1497
|View full text |Cite
|
Sign up to set email alerts
|

Solar Oblateness, Excess Brightness, and Relativity

Abstract: New observations show a small difference between the sun's polar and equatorial limb darkening functions. This excess equatorial brightness varies in time and can be of sufficient magnitude to account for the solar oblateness inferred by Dicke and Goldenberg from their measurements. This removes the serious consequence of their work for Einstein's general theory of relativity. The problems of a solar-edge definition and the derivation of a solar mass quadrupole moment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Hill, a former colleague of Dicke who had helped build the instrument with which the 1964 observations were made (Dicke, 1964), and collaborators, also attempted to measure the solar oblateness, using an instrument, SCLERA [Santa Catalina Observatory for Experimental Relativity by Astrometry], which was later to play a role in the early days of helioseismology. This measurement, carried out in 1973, (Hill and Stebbins, 1975), found a 9.6 × 10 −6 value for the oblateness, much smaller than that of Dicke and Goldenberg (1967b); Hill et al (1974) also pointed out a time-varying difference between the brightness of the solar limb and poles that might account for the anomalously high oblateness measurement. Ulrich and Hawkins (1981a,b) made an early attempt to deduce what the J 2 and J 4 terms should be based on a simple differential rotation profile deduced from surface measurements, obtaining predicted values of between 1 and 1.5 × 10 −7 for J 2 and between 2 and 5 × 10 −9 for J 4 depending on the size of the convective envelope.…”
Section: The Oblateness Controversymentioning
confidence: 78%
“…Hill, a former colleague of Dicke who had helped build the instrument with which the 1964 observations were made (Dicke, 1964), and collaborators, also attempted to measure the solar oblateness, using an instrument, SCLERA [Santa Catalina Observatory for Experimental Relativity by Astrometry], which was later to play a role in the early days of helioseismology. This measurement, carried out in 1973, (Hill and Stebbins, 1975), found a 9.6 × 10 −6 value for the oblateness, much smaller than that of Dicke and Goldenberg (1967b); Hill et al (1974) also pointed out a time-varying difference between the brightness of the solar limb and poles that might account for the anomalously high oblateness measurement. Ulrich and Hawkins (1981a,b) made an early attempt to deduce what the J 2 and J 4 terms should be based on a simple differential rotation profile deduced from surface measurements, obtaining predicted values of between 1 and 1.5 × 10 −7 for J 2 and between 2 and 5 × 10 −9 for J 4 depending on the size of the convective envelope.…”
Section: The Oblateness Controversymentioning
confidence: 78%
“…The solar quadrupole moment also plays a role in general relativity (Hill et al 1974) and in celestial mechanics. The relativistic precession of the perihelion of planets is a known phenomenon (Pireaux & Rozelot 2003), ∼43 arcsec per century in the case of Mercury.…”
Section: Relativistic Celestial Mechanicsmentioning
confidence: 99%
“…All such models must eventually satisfy several general observational constraints. Among these are (1) differential rotation; (2) practically uniform radiant energy output, i.e., variation with latitude less than a few parts in 103 [Caccin et al, 1970;Altrock and Canfield, 1972;Noyes et al, 1973;Peraiah, 1973;Hill et al, 1974]; and (3) a hydromagnetic dynamo action that provides the basic observed characteristics of the activity cycle--or at least a model that does not interfere with some other mechanism that does. cock, 1961;Krause and R/idler, 1971;Roberts and Stix, 1972;Stix, 1976; Yoshimura, 1978] can obtain reasonable agreement with observed properties of the cycle only with a rotation rate that increases inward at least in the upper.convection zone.…”
Section: Theorymentioning
confidence: 99%